An analytic hierarchy process approach in the shortlisting of job candidates in recruitment - Gustilo, Reggie C. (Animo Repository, 2019)
The analytical hierarchy process (AHP) is an intelligent and mathematical tool to improve the shortlisting process of organizations in recruiting skilled and competent employees. This reduces time-consuming recruiting activities by allowing it to rate, rank and shortlist candidates in a fair and objective manner especially from an applicant pool with various credentials. Job candidates are measured on the identified criteria namely; education, work experience, position level and professional qualification that are methodically weighted according to their importance. Subsequently, comparison matrixes measure the characteristics of each individual by creating a functional hierarchy and receives a final decision score. The contribution of this article was to provide a systematic and effective analysis on complex issues by specifying results by obtaining numerical decisions based on firm criteria preferences on the shortlisting process that is tunable to assist organizations to make better and proactive decisions in lesser time and cost in attracting and retaining quality employees. © 2019, World Academy of Research in Science and Engineering. All rights reserved.